VD_FINDINFO HC / 2010 / 714 vom 5. November 2010 - VD Tribunal cantonal (2010)
OBLIGATION D'ENTRETIEN, PERSONNE DIVORCÉE, LIQUIDATION DU RÉGIME MATRIMONIAL, DÉPENS | 121 al. 3 CC, 125 al. 1 CC, 125 CC, 205 al. 2 CC, 92 al. 2 CPC, 92 CPC